Equity of participants in clinical trials in critical care and perioperative medicine research: a systematic review - Joanna Kae Ling Wong; Caroline Thomas; Hannah Gravett; Kavi Thobhani; Ayah Mekhaimar; Jan Man Wong; Yize Isalina Wan (BJA Open, 2025)
Background: Underrepresentation in critical care and perioperative randomised controlled trials (RCTs) limit generalisability and drive health inequity. This systematic review of large, high-quality RCTs analysed representation and reporting trends of equity data over 10 yr. Methods: We searched MEDLINE, Embase, and Clinicaltrials.gov between 01 January 2013 and 11 May 2023 for RCTs recruiting adults (age ≥18 yr) receiving a critical care/perioperative intervention. We examined study characteristics, completeness of participant characteristic reporting, considerations accounting for participant characteristics, differential missing data rates, participant representativeness, and considerations to improve equitable recruitment. Participant characteristics were defined using the PROGRESS framework: Place of residence, Race/ethnicity/culture/language, Occupation, Gender/sex, Religion, Education, Socioeconomic status, and Social capital. We assessed risk of bias using the Cochrane Risk of Bias 2 tool. Results: We included 60 trials (52 critical care, eight perioperative medicine) involving 155 036 participants. Mean (sd) age was 62.9 (4.1) yr. Gender/sex (n=59, 98.3%), race/ethnicity (n=10, 16.7%), place of residence (n=1, 1.7%), and social capital (n=1, 1.7%) were reported in trials. Statistical considerations were made for gender/sex in nine (15.0%) trials. Gender/sex data were missing in two trials with 5.0% and 0.3% missingness. Race/ethnicity data were missing in seven trials, with 7.39% (inter-quartile range 0.4–19.2%) missingness. Trials underrepresented female and non-White participants compared with baseline populations. No trial explicitly stated efforts to improve equitable recruitment. Conclusions: Large, high-quality critical care and perioperative RCTs inconsistently collect and report equity data. Female and non-White participants are underrepresented. These findings potentially limit generalisability of research findings. Further work is required to promote equitable study designs. Systematic review protocol: PROSPERO (CRD42023401126)